Perceptions of plain packaging and health warning labels for cannabis among young adults: findings from an experimental study - Seema Mutti-Packer; Brianne Collyer; David C. Hodgins (BMC, 2018)
Abstract Background There is strong evidence that plain cigarette packaging and health warning labels (HWLs) reduce brand appeal and increase health knowledge. There is limited evidence examining this population-level public health approach for cannabis packaging. This issue is of particular importance in light of the recent legalization of recreational cannabis in Canada. The current study examined perceptions of plain packaging and HWLs for cannabis packages among young adults. Methods An online experimental study was conducted with a sample of university students in Alberta, Canada (n = 656). Respondents were randomly assigned to view cannabis packages in one of four conditions: Condition 1: branded pack, Condition 2: plain pack (uniform color, brand imagery removed, standardized font), Condition 3: branded pack with a HWL, and Condition 4: plain pack with a HWL. Respondents in Conditions 3 and 4 viewed five text-based HWLs, each corresponding to a health effect associated with cannabis use: (1) brain development, (2) mental health issues, (3) impaired driving, (4) nonlethal overdose, and (5) addiction. After viewing packs, respondents rated packs and health warnings on various measures. Results Branded packages without HWLs were rated as most appealing compared to all other packs (p < 0.001 for all contrasts). No differences were found in ratings of appeal when comparing branded and plain packs with HWLs. Warning messages for cognitive development and impaired driving were rated highest on levels of perceived effectiveness, believability, and fear, whereas the addiction warning was rated among the lowest. In general, there were gaps in health knowledge related to cannabis use, however after viewing packs with warnings (compared to viewing packs without warnings) levels of health knowledge increased across all health effects (p < 0.01 for all). Lastly, a significant majority of young adults reported they would purchase the branded pack without a HWL (39.5%), compared to all other pack types (p < 0.05 for all contrasts). The lowest proportion of young adults reported they would purchase a plain pack with a HWL (1.1%). Conclusions Plain packaging and health warnings may reduce brand appeal and increase health knowledge among young adults.